Determinasi Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Manggarai Barat - Seman, Hilarius; Afrino, Yonas; Yuliani, Priska; Wahyudi, Agus (LPPM Universitas Bina Sarana Informatika, 2025)
This study aims to examine the effect of the implementation of a regional financial accounting system, human resource competency, information technology utilization, and internal control on the quality of financial reports. This study is a quantitative study with an associative approach. The population in this study were all employees in the finance or accounting department of the Regional Apparatus Organization in West Manggarai Regency. The sampling technique in this study was saturated sampling, namely the entire population was sampled with a total of 60 respondents. The data collection technique used questionnaires to all respondents. Data analysis used multiple linear regression analysis. The results of the study partially showed that human resource competency and internal control had a positive effect on the quality of financial reports in the Regional Government of West Manggarai Regency. Meanwhile, the regional financial accounting system and information technology did not affect the quality of financial reports in the Regional Government of West Manggarai Regency. Simultaneously, the variables of the implementation of a regional financial accounting information system, human resource competency, information technology utilization, and internal control had a positive effect on the quality of financial reports in the Regional Government of West Manggarai Regency. The results of the determination test indicate that the quality of financial reports can be explained by the variables of the implementation of the regional financial accounting system, human resource competence, utilization of information technology, and internal control as much as 68.2%, while the remaining 31.8% is influenced by explained by other variables not included in this study. The implication of the research results is the need for an evaluation of the implementation of the regional financial accounting system currently used. The use of the system needs to be optimized comprehensively to ensure good integration between work units.